2012
DOI: 10.4103/0189-6725.99396
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of paediatric achalasia in India: Single centre experience

Abstract: Cardiomyotomy with partial fundoplication is the best modality of treatment for paediatric achalasia cardia, even from parents' perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…[ 13 ] The mean age at surgery in our study was consistent with other pediatric studies such as Erginel et al , Lee et al , Hallal et al , Corda et al , Karnak et al , Singh et al , Smits et al , Zagory et al , and Saliakellis et al as they reported mean age at surgery of 3.34 years, 13 ± 6 years, 11 years, 12 years, 8.3 years, 3.25 ± 0.4 years, 11.4 ± 3.4 years, 11.6 ± 5 years, and 10 years, respectively. [ 2 7 14 15 16 17 18 19 20 ] There was no gender predilection in adult studies while the pediatric studies showed a male preponderance. [ 2 3 7 14 15 16 17 18 19 20 ] However, our study showed a female preponderance (9:3).…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] The mean age at surgery in our study was consistent with other pediatric studies such as Erginel et al , Lee et al , Hallal et al , Corda et al , Karnak et al , Singh et al , Smits et al , Zagory et al , and Saliakellis et al as they reported mean age at surgery of 3.34 years, 13 ± 6 years, 11 years, 12 years, 8.3 years, 3.25 ± 0.4 years, 11.4 ± 3.4 years, 11.6 ± 5 years, and 10 years, respectively. [ 2 7 14 15 16 17 18 19 20 ] There was no gender predilection in adult studies while the pediatric studies showed a male preponderance. [ 2 3 7 14 15 16 17 18 19 20 ] However, our study showed a female preponderance (9:3).…”
Section: Discussionmentioning
confidence: 99%
“…It is a chronic but benign disease of an unknown etiology and is a common cause of dysphagia ( 3 ). The most common symptoms of Achalasia are regurgitation, vomiting, dysphagia, cough, recurrent pneumonia, and poor weight gain or weight loss ( 1 , 2 , 4 ). The “bird’s beak” appearance of the lower esophagus on the esophagogram (barium swallow) is a classical radiological finding in the cases of esophageal Achalasia ( 1 , 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most common symptoms of Achalasia are regurgitation, vomiting, dysphagia, cough, recurrent pneumonia, and poor weight gain or weight loss ( 1 , 2 , 4 ). The “bird’s beak” appearance of the lower esophagus on the esophagogram (barium swallow) is a classical radiological finding in the cases of esophageal Achalasia ( 1 , 2 , 4 ). Achalasia is rare in children, with an estimated annual incidence of only 0.02–0.11 cases per 100 000 children, and it is more infrequent in the below 5-year age group ( 1 , 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall incidence of achalasia is 1.63 : 100 000, fewer than 5% of whom are children [4, 5]. However, young age at presentation is an independent predictive factor of failure of conservative treatment [6].…”
Section: Introductionmentioning
confidence: 99%